Analisis Pengaruh Keterlibatan Kerja dan Kepuasan Kerja terhadap Organizational Citizenship Behavior di PT Prima Graphia Digital - Andrew Adi Saputra; Liemdra Hendro Yono; Laksmi Sito Dwi Irvianti (Binus Business Review, 2013)
PT Prima Graphia Digital is a company engaged in the area of digital printing, locates at Kalibaru Timur Street IV No 5-7, Senen, Central Jakarta, Indonesia, 10460. The purpose of this research is to analyze the effect of job involvement and work satisfaction towards Organizational Citizenship Behavior in PT. Prima Graphia Digital. Research used associative method. Data used were primary and secondary data obtained through observation, interview and questionnaire distribution to 86 staffs of the company as respondents. After obtaining the data, then data were processed using Pearson correlation, simple and multiple regression. Results showed that job involvement has positive effect and is significant towards Organizational Citizenship Behavior. Similarly, work satisfaction does also have a positive effect and is significant towards Organizational Citizenship Behavior. Furthermore, job involvement and work satisfaction simultaneously have a significant effect towards Organizational Citizenship Behavior.